2016
DOI: 10.1590/1809-98232016019.160013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Oral Health Profile of Institutionalized Elderly Persons in Brazil and Barcelona, Spain

Abstract: Objective: To compare the oral health profile of institutionalized elderly persons in Brazil and in Barcelona, Spain, by gender and country of residence. Methods: A cross-sectional study was performed of individuals aged 65 years and above (n=1,440), resident in the health region of Barcelona and in Brazil. Two surveys and exams relating to the oral health status of institutionalized elderly persons in Brazil (in 2008) and in Barcelona, Spain (in 2009) were carried out. Periodontal disease, tooth loss and dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Studies have indicated that self-perception may contribute to the direction and planning of dental services 19,20, contrary to the results presented herein since self-perception was positive even in the presence of precarious clinical conditions. This may be because most elderly people (and also their caregivers and family members) tend to consider oral issues secondary to other systemic problems 9,21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that self-perception may contribute to the direction and planning of dental services 19,20, contrary to the results presented herein since self-perception was positive even in the presence of precarious clinical conditions. This may be because most elderly people (and also their caregivers and family members) tend to consider oral issues secondary to other systemic problems 9,21.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the majority of elderly people, whether institutionalized or not, tend to dismiss oral health services because they believe that they no longer need/deserve this type of care, which aggravates their condition and their self-perception of health 4,5,7. This attitude may affect orofacial pain associated with lifestyle and habits and the quality of life 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…3 In contrast to the increase in institutionalization rates, few public policies are related to institutionalized elderly individuals. 4 In addition, few caregivers are trained to perform oral care for dependent institutionalized elderly individuals. 4,5 Nevertheless, these factors can impair the oral health of such a population.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, few caregivers are trained to perform oral care for dependent institutionalized elderly individuals. 4,5 Nevertheless, these factors can impair the oral health of such a population. 5 In this context, poorer oral health conditions have been reported in elderly individuals residing in long-term care institutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the poor oral health profile of Brazilian elderly people 2 has called attention of other health professionals who interact with this population more often than dentists 3 . Their concern is because oral health may affect and be affected by systemic health, generating physical and psychosocial effects 4 .…”
Section: Introductionmentioning
confidence: 99%